Approach Implementationcontextual Teaching and Learning and Its Implications on Student PAI Learning Activities at Madrasah Aliyah Ibnu Rusyd Cileunyi Bandung - Sahliah, Sahliah (Pusat Penerbitan Universitas (P2U) Unisba, 2023)
Low learning process is the main problem in learning. In this case the teacher uses the Contextual Teaching and Learning learning model. The purpose of this research is to reveal the innovation efforts of Islamic religious education (PAI) learning through the contextual teaching and learning (CTL) learning model in improving the quality of PAI learning at Madrasah Aliyah Ibnu Rusyd Cileunyi Bandung. The focus of his research is the planning of contextual teaching and learning models in improving the quality of learning, and the quality of PAI learning is the goal of the contextual teaching and learning model at Madrasah Aliyah Ibnu Rusyd Cileunyi Bandung. This study uses a qualitative approach to the type of case study. Interviews, observations, and documentation were used to collect data. Then, the data were analyzed by reducing, presenting, and drawing conclusions. The results of the study show that: learning planning through the contextual teaching and learning model is carried out by taking into account the suitability of KD with methods, materials and models, selecting learning media and learning resources and the right approach. In implementing the learning process berorientation to students (student-centered through stagesConstructivism (Constructivism), Find (Inquiry), Learning Society (Learning Community), Modeling (Modeling) and the actual assessment (authentic). The quality of PAI learning through contextual teaching and learning, namely; teachers can build students' positive attitudes towards lessons, student-centered learning has a positive impact on learning so that students are motivated to learn and experience directly in learning so as to enhance the learning experience.